The Twain is Crossing:: Barbie's Existential Crisis Portrayed in Barbie 2023 Movie - Elhaq, Melia (LITERA KULTURA : Journal of Literary and Cultural Studies, 2024)
The feelings of anxiety and anomalies experienced by the ‘Stereotypical Barbie’ in her perfect world calledBarbie-land, make her question her existence. This study focused on Simone de Beauvoir’s theory ofexistentialism depicted in the women characters of Barbie 2023 movie directed by Greta Gerwig. The aim of thisstudy is to explore the existential crisis experienced by the women characters. Barbie’s journey on the real -worldfinally discovers that her existential crisis arises from the anomalies that are affected by imperfect externalhuman experience when the “twain is crossing”. Barbie represents the principles of existentialist feminism asdefined by Simone de Beauvoir by confronting these existential concerns.